Research on accurate ranging of UWB under indoor environments - WU Shao-hua; ZHANG Nai-tong (Tongxin xuebao)
The accurate ranging ability of ultra wideband（UWB） signal under IEEE 802.15.4a indoor channel model was studied.An improved time-of-arrival（TOA） estimation algorithm which utilizes region search and threshold comparison was proposed.By statistical analysis on certain characteristics of the CM1 and CM2 channel profiles,the probability model of TOA estimation error was deduced.The thresholds of the proposed TOA estimation algorithm were then set by limiting the error probability to the lowest level.The mean absolute ranging errors under different SNR were simulated.Results show that high enough SNR should be guaranteed in order to obtain centimeter-level ranging precision under in-door environments,while extremely high SNR would not help to improve the ranging precision any more but lead to a performance floor.The results have instructional significance on designing localization algorithms and transmission power control in practical ranging.